Environmental Sustainable Utilization of Agricultural Waste–Based Sterilization for White Oyster Mushroom Cultivation: An FTIR Study of Optical Vibrational Properties - Irzaman; Erni Apriliana; Ridwan Siskandar; Heriyanto Syafutra; Renan Prasta Jenie; Marina Indriasari; Muhammad Mahyiddin Ramli; Nazopatul Patonah Har; Muammar Mohamad Isa (CV FOUNDAE, 2026)
This study investigates the environmentally sustainable use of agricultural waste–based sterilization in white oyster mushroom (Pleurotus ostreatus) cultivation and its influence on mycelial optical vibrational properties. A small-scale industrial rice husk furnace was employed as an eco-friendly and low-cost sterilization system, providing an alternative to conventional fossil fuel–based energy sources. Potato Dextrose Agar (PDA) was used as the growth medium, while different sterilization levels were applied to obtain uncontaminated media and high-quality mycelial growth. Three sterilization levels were systematically analyzed using Fourier Transform Infrared (FTIR) spectroscopy to evaluate optical behavior at various cultivation stages. The optical properties of the mycelium were assessed through Longitudinal Optical (LO) and Transverse Optical (TO) vibrational modes derived from FTIR spectra. The results indicate that increasing the sterilization level leads to a consistent shift of both LO and TO modes toward higher wavenumbers, reflecting changes in molecular bonding and structural characteristics of the mycelium. Furthermore, longer boiling durations at 102 °C using the rice husk furnace resulted in higher transmittance values, attributed to the partial evaporation or reduction of certain organic compounds within the mycelium. Comparative analysis among cultivation stages shows that the planting spawn (F2) exhibits lower transmittance than the spreading spawn (F1), while the pure culture (F0) demonstrates the highest transmittance. These differences are closely related to variations in mycelial density, with F2 having the greatest mass per unit volume. Overall, the findings confirm that agricultural waste–based sterilization supports environmentally sustainable mushroom cultivation while significantly affecting the optical and structural properties of mycelium.